Transformation of Religious Education Policy in Indonesia: From Dominance to Confessional Pluralism - Shodikin, Eko Ngabdul; Ruwandi; Saerozi, Muh (el-Tarbawi, 2025)
This study examines the transformation of religious education policy in Indonesia from the dominance of one religion to a more inclusive and dialogical confessional pluralism. This issue is important because, for decades, religious education policy has reflected a hegemonic orientation favoring one religion, potentially creating social segregation and hindering the development of interfaith tolerance. Using a literature study method with thematic and content analysis, this study examines various academic sources, national policy documents, and educational frameworks to identify patterns of paradigm shift, driving factors, and challenges in the implementation of religious education policy in Indonesia. The research findings indicate a substantial paradigm shift from faith-based teaching focused on doctrinal knowledge and ritual observance to a humanistic model emphasizing moral values, religious moderation, and civic character formation. Post-reform socio-political dynamics, globalization, and national initiatives such as Religious Moderation and the Pancasila Student Profile program drive this transformation. However, the implementation of confessional pluralism still faces ideological, structural, and cultural obstacles, including resistance to pluralist values ​​and limited teacher capacity. This study concludes that religious pluralism represents a new paradigm that positions religious education as a strategic instrument for building an inclusive, moderate, and civilized society. These findings reinforce the urgency of religious education reform as a foundation for strengthening social cohesion and interfaith harmony in Indonesia.